2021
DOI: 10.3389/fimmu.2021.639092
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Antiviral Pathways of the Silkworm Bombyx mori

Abstract: The lepidopteran model silkworm, Bombyx mori, is an important economic insect. Viruses cause serious economic losses in sericulture; thus, the economic importance of these viruses heightens the need to understand the antiviral pathways of silkworm to develop antiviral strategies. Insect innate immunity pathways play a critical role in the outcome of infection. The RNA interference (RNAi), NF-kB-mediated, immune deficiency (Imd), and stimulator of interferon gene (STING) pathways, and Janus kinase/signal transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 87 publications
0
35
0
Order By: Relevance
“…The pathway is conserved throughout biological evolution and plays an important role in insect innate immunity [ 141 , 142 ]. Numerous studies have revealed its involvement in intestinal immune responses, such as resistance to viral infections [ 143 , 144 , 145 , 146 ] and resistance to fungal and bacterial infections [ 147 , 148 ].…”
Section: Intestinal Immunity Responsementioning
confidence: 99%
“…The pathway is conserved throughout biological evolution and plays an important role in insect innate immunity [ 141 , 142 ]. Numerous studies have revealed its involvement in intestinal immune responses, such as resistance to viral infections [ 143 , 144 , 145 , 146 ] and resistance to fungal and bacterial infections [ 147 , 148 ].…”
Section: Intestinal Immunity Responsementioning
confidence: 99%
“…However, a single-cell RNA-sequencing study of BmNPV-infected hemocytes in B. mori has shown suppression of the RNAi pathway by the virus [ 61 ]. These studies highlight the role of the RNAi pathway in B. mori hemocytes; however, its direct involvement in the antiviral defense remains unclear [ 62 ].…”
Section: Antiviral Immune Pathway In Hemocytesmentioning
confidence: 99%
“…The alkalinity of the silkworm midgut triggers the dissolution of OBs and the release of ODV in the midgut lumen. The ODV is responsible for the primary infection through oral transmission of the virus among silkworm larvae, while the BV is responsible for the secondary infection, causing systemic spreading all over the host within the infected silkworm larvae ( Jiang, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bombyx mori is a model organism, and BmNPV is a typical baculovirus ( Gomi et al, 1999 ; Mita et al, 2004 ; Xia et al, 2004 ), and together, they present an important model to assess host–baculovirus interactions ( Jiang and Xia, 2014 ). Insights from previous host studies revealed that innate antiviral immunity in lepidopteran insects plays important roles in host–baculovirus interactions ( Jiang, 2021 ). Antiviral proteins, including red fluorescent proteins (RFPs) ( Sunagar et al, 2011 ; Manjunatha et al, 2018 ), Bmlipase (Bmlipase-1 and Bmlipase member H-A) ( Ponnuvel et al, 2003 ; Zhang S. Z. et al, 2020 ), serine proteases (SPs), and serine protease homologs (SPHs) ( Nakazawa et al, 2004 ; Ponnuvel et al, 2012 ), show strong antiviral activity in the digestive juice of the silkworm.…”
Section: Introductionmentioning
confidence: 99%